The Spy - Cussler, Clive; Scott, Justin (New York : G.P. Putnam's Sons, 2010)
In 1908, a brilliant American battleship gun designer dies in a sensational apparent suicide. The man's grief-stricken daughter turns to the legendary Van Dorn Detective Agency to clear her father's name. Van Dorn puts his chief investigator on the case, and Isaac Bell soon realizes that the clues point not to suicide but to murder.
Includes illustrations on lining papers.
Accelerated Reader AR
Keywords: Bell, Isaac (Fictitious character) -- Fiction; Private investigators -- Fiction; Sabotage -- Fiction; Railroad trains -- Fiction; Washington (D.C.) -- Fiction -- History -- 20th century; Adventure fiction; Suspense fiction